BERPOLITIK LEWAT PARTAI POLITIK : Ulasan Etis atas Suatu Bentuk Manifestasi Politik - Sakti, Philips Rusihan (LOGOS, 2003)
Aristotle said that human being is a zoon politikon (commonly understood as "social being"). How does his/her political dimension express itself in real life within society? Since political dimension has something to do with society as a whole, thus anyone actually has a political attitude and already acts politically as far as his/her attitude and doing affect society. In this sense, being active in a political party or the party itself can be considered as a manifestation of human nature as political being, precisely because the party has society as its orientation. Political Ethic first of all wants to search and determine fundamental norms and principles of managing a society and governing a state. Every political party and government then must observe these norms and principles. They are principle of equality, principle of freedom, principle of solidarity and principle of utility. These four principles have to be followed by the state, while performing the principle of subsidiary. Furthermore the state has a duty and responsibility to accomplish social welfare and guarantee social justice. So, what is the task of political party? On one hand, maintaining all the fundamental principles and state's duties above mentioned, it has to control and influence the actual government, if it isn't part of this. On the other, it must preserve all those ethical norms while performing the state's governance, in case it holds the government or takes part of it.